PERANCANGAN DAN PELAKSANAAN MODEL PEMBELAJARAN MATEMATIKA YANG KONTRUVISTIK, KONTEKSTUAL DAN KOLABORATIF PADA MATERI POKOK TRIGONOMETRI DI SMKN 5 SEMARANG - Achmad Buchori; Widya Kusumaningsih (Universitas PGRI Semarang, 2011)
This research?é?áaims?é?áto?é?áproduce?é?áa design?é?áthat?é?áconstructivist?é?ámodel of?é?álearning mathematics, contextual?é?áand?é?ácollaborative?é?áin the?é?ásubject matter?é?áin class?é?áX?é?áTrigonometry SMK has been tested?é?áin the classroom.?é?áThis research was conducted?é?áby?é?áaction research?é?ámethods?é?áclass,?é?áin class X SMKN?é?á5?é?áSemarang?é?áCentral Java. The first lesson plan (RP)?é?á?é?áneeds to be evaluated?é?áearly?é?áand corrected?é?áin terms of?é?áclassroom?é?ámanagement?é?áto?é?ábe a?é?áLesson Plan?é?á(RP)?é?áfinal.?é?áTeachers should?é?ákeep students attention to?é?áorientation activities?é?ádespite?é?áhurried?é?áexploration activities, it is necessary?é?áto control the?é?áactivities of?é?áexploration?é?áand?é?ánegotiation?é?áin order to run?é?áefficiently and?é?ánegotiation?é?áactivities?é?áneed?é?áto be?é?ádone?é?áto get?é?áattention. Students?é?áseem?é?áready?é?áto make?é?áchanges to?é?áthe learning?é?áactivities,?é?ácan appear within?é?áa given?é?áproblem-solving strategies,?é?ádaring?é?áto?é?áshow?é?áwork?é?áand discuss it,?é?ádare?é?áto present?é?áthe work of?é?áthe group and?é?á discuss?é?áand?é?ánegotiate. Key Words:?é?áLearning Model,?é?áConstructivist,?é?áContextual,?é?áCollaborative, Trigonometry